Analisis Pengaruh Debit dan Dosis FeSO4 Terhadap Penghilangan Cr6+ Pada Sistem Pengolahan Air Limbah Industri Pertambangan Nikel - Reonald Adhi Wibowo; Tuhu Agung Rachmanto (Teknik Lingkungan, Institut Teknologi Adhi Tama Surabaya, 2026)
This study aims to analyse the relationship between flow rate and FeSO₄ dosage on the amount of Cr⁶⁺ load treated in a nickel mining wastewater treatment system. Data was obtained from seven Sediment Ponds (SDPs) operating in the mining area. The parameters analysed included flow rate (m³/day), actual FeSO₄ dosage (kg/day), and influent and effluent Cr⁶⁺ loads (kg/day). The treated Cr⁶⁺ load was calculated from the difference between the influent and effluent loads at each SDP. Correlation and regression analyses were used to examine the operational trends between variables. The results showed that the flow rate had a linear relationship with the treated Cr⁶⁺ load because the load parameter was mathematically dependent on the flow rate. The FeSO₄ dosage showed a strong positive relationship with the treated Cr⁶⁺ load, reflecting the operational adjustment between coagulant requirements and pollutant load. These findings provide a technical overview that the proportional adjustment of flow rate and chemical dosage is an important aspect in the effectiveness of the Cr⁶⁺ reduction process in mine wastewater treatment systems.